2022
DOI: 10.1155/2022/5120569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinical Nursing Pathway Intervention Based on Evidence-Based Medicine on Venous Thrombosis in Long-Term Bedridden Patients

Abstract: Background. Venous thrombosis is a type of medical condition that establishes as deep vein thrombosis of the limb or pulmonary embolism. This disease arises as a result of interrelating hereditary, ecological, and interactive risk aspects. Clinical nursing pathways also known as critical pathways are pathways that guide nurses when developing a patient’s care plan. However, the effect of nursing intervention on venous thrombosis in long-term bedridden patients from the perspective of evidence-based medicine ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Effective nursing intervention is an important means to improve the quality of life of EC patients [ 23 ]. Clinical nursing pathway has been widely used in brain department, liver department, and critical ICU and achieved better nursing effects [ 24 ]. Clinical nursing path refers to the treatment and nursing mode developed by specialists, responsible nurses, psychological consultants, and dietitians according to diseases or surgeries and approved by relevant medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Effective nursing intervention is an important means to improve the quality of life of EC patients [ 23 ]. Clinical nursing pathway has been widely used in brain department, liver department, and critical ICU and achieved better nursing effects [ 24 ]. Clinical nursing path refers to the treatment and nursing mode developed by specialists, responsible nurses, psychological consultants, and dietitians according to diseases or surgeries and approved by relevant medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…The "2021 Practice Standards for Infusion Therapy" [10] has encouraged patients with indwelling PICCs to perform early, normal daily activities, and mild physical exercise, but it has not specify the specific early hand activity program. There are many researches [11][12][13] on the methods and modes of limb exercise on the side of PICC catheterization worldwide, hand and upper limb exercises are widely used in clinical practice for prevention, but there is no quantitative standard for the duration, frequency, and frequency of exercise. Several previous studies [14][15][16] have reported the effects of quantified versus willful grip exercises for the prevention of PICC-related thrombosis, yet the results remain inconsistent.…”
Section: All Data Generated or Analyzed During This Study Are Include...mentioning
confidence: 99%
“…As a component of the advancement in the field of nursing science, the traditional approach to nursing based on experience is undergoing a transformation into the modern approach of nursing that is grounded in scientific principles. There exist various sources of evidence that can be followed, which have the potential to offer a more comprehensive and scientifically informed framework for guiding nursing practice (Chen et al, 2022). DVT continues to pose a challenge for individuals, primarily due to the insufficient knowledge and inadequate implementation of preventive measures by nurses (Alyousef, et al, 2022 2022), nurses are the most suitable candidates for conducting daily assessments of DVT prophylaxis.…”
Section: )mentioning
confidence: 99%